Will containment of wild poliovirus in laboratories and inactivated poliovirus vaccine production sites be effective for global certification? - Walter R. Dowdle; Christopher Wolff; Raymond Sanders; Scott Lambert; Maureen Best
The absolute laboratory containment of any virus cannot be guaranteed, but a wealth of experience indicates that effective containment of wild poliovirus materials for global certification is technically and operationally feasible. Effective containment is based on the principles of minimal wild poliovirus infectious and potentially infectious materials in laboratories; minimal risks of operations in laboratories and inactivated poliovirus vaccine production facilities; minimal susceptibility of workers to wild poliovirus infection and shedding; and minimal susceptibility of populations to wild poliovirus spread. Each principle alone is imperfect, but collectively they greatly minimize the risks of transmitting wild poliovirus from the laboratory to the community.